L-arginine and L-lysine degrade troponin-T, and L-arginine dissociates actomyosin: Their roles in improving the tenderness of chicken breast. (15th July 2020) - Zhang, Yinyin; Zhang, Daojing; Huang, Yajun; Chen, Li; Bao, Pengqi; Fang, Hongmei; Zhou, Cunliu
Highlights: Arginine/lysine reduced the shear force of chicken breast. Arginine/lysine increased the pH value and sarcomere length. Arginine/lysine raised the myofibrillar fragmentation index. Arginine/lysine degraded troponin-T by maintaining calpain activity. Arginine dissociated chicken actomyosin and decreased Ca 2+ /Mg 2+ -ATPase activities. Abstract: This work investigated the effects of L-arginine (Arg) and L-lysine (Lys) on the tenderness of chicken breast and explored the possible mechanisms underlying this effect for the first time. The results showed that both Arg and Lys decreased the shear force and increased the pH value, sarcomere length and myofibrillar fragmentation index as well as degraded the troponin-T by keeping calpain activity in chicken breast. In addition, Arg effectively reduced Ca 2+ /Mg 2+ -ATPase activities and promoted actomyosin dissociation. These results indicated that both Arg and Lys could enhance the tenderness of chicken breast, and it could also explain why Arg was more effective than Lys in improving the tenderness of chicken breast. These results will help facilitate the development of industrial-scale methods for improving the tenderness of meat products.